Geodynamic setting of Scotia Sea and its effects on geomorphology of South Sandwich Trench, Southern Ocean - Lemenkova, Polina (Polish Polar Research, 2021)
The South Sandwich Trench located eastward of the Drake Passage in the Scotia Sea between Antarctica and South America is one of the least studied deep-sea trenches. Its geomorphological formation and present shape formed under the strong influence of the tectonic plate movements and various aspects of the geological setting, i.e., sediment thickness, faults, fracture zones and geologic lineaments. The aim of this paper is to link the geological and geophysical setting of the Scotia Sea with individual geomorphological features of the South Sandwich Trench in the context of the phenomena of its formation and evolution. Linking several datasets (GEBCO, ETOPO1, EGM96, GlobSed and marine free-air gravity raster grids, geological vector layers) highlights correlations between various factors affecting deep-sea trench formation and development, using the Generic Mapping Tools (GMT) for cartographic mapping. The paper contributes to the regional studies of the submarine geomorphology in the Antarctic region with a technical application of the GMT cartographic scripting toolset.